Phytochemical Screening and Antioxidant Potential of 70% Ethanol Extract, n-Hexane Fraction, Ethyl Acetate Fraction and Methanol:Water Fraction of Gotu Kola Leaves (Centella asiatica) - Erlin Saalino; Halifah Pagarra (bionature, 2023)
This research aims to examine the phytochemical content and antioxidant potential of 70% ethanol extract of Centella asiatica leaves and the results of fractionation using 3 types of solvents with different polarities. Centella asiatica leaves were extracted by maceration method, then fractionation and phytochemical screening were carried out. Test the total phenolic content with the Folin Ciocalteu method and antioxidant activity with the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The yield of 70% ethanol solvent maceration, n-hexane fraction, ethyl acetate fraction and methanol fraction were 18.782%, 3.05%, 6.19%, 92.46%. Phytochemical screening of 70% ethanol extract of Centella asiatica leaves contains flavonoids, tannins, phenolics, alkaloids and steroids. The n-hexane fraction contains alkaloids, tannins, phenolics and triterpenoids. The ethyl acetate fraction contains flavonoids, saponins, tannins, phenolics, alkaloids and steroids. The methanol:water fraction contains alkaloids, flavonoids, saponins, tannins, phenolics and triterpenoids. The total phenolic content test of 70% ethanol extract, n-hexane fraction, ethyl acetate fraction and methanol:water fraction was 12.773 ± 0.479 mg GAE/g, 1.182 ± 0.124 mg GAE/g, 18.334 ± 0.305 mg GAE/g, 10.211 ± 0.247 mg GAE/g. Antioxidant activity of 70% ethanol extract, n-hexane fraction, ethyl acetate fraction and methanol:water fraction with IC50 values of 77.4 ppm, 2122,5 ppm, 45.6 ppm and 126 ppm.